The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.25073/2588-1116/vnupam.4093
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric in Advertising

Abstract: Advertising mobilizes many methods relevant to three fundamental elements of rhetoric such as Ethos, Pathos and Logos by using, for example rhetorical figures such as special images, unusual words, and arrangement of information leading to desirable deduction and strong emotion. Methods using images are more efficient than traditional ones using words. They are known as visual rhetoric. In television advertising, the most used rhetorical figures are repetition, hyperbole, metaphor, and comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Rhetoric provokes positive attitude and favorable emotions. (Vu, 2017)If we study the advertisements we can conclude that both visual and verbal are an important part of advertisements that we encounter in any form and at any platform. It has been proposed by many researchers that imagery is a part and parcel of advertisement in relation to effective consumer response (Greenberg & Garfinkle, 1963).The recent latest literature review suggests that there is an inclination of researchers towards the role of visuals and imagery in the effectiveness of advertisements in such a way that there has been methodological study and analysis on the significance of non-verbal cues in the rhetoric of advertisements (Swasy & Munch, 1985), (Scott, 1994a) Visual elements are analyzed in this research by drawing upon the Archival tradition.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Rhetoric provokes positive attitude and favorable emotions. (Vu, 2017)If we study the advertisements we can conclude that both visual and verbal are an important part of advertisements that we encounter in any form and at any platform. It has been proposed by many researchers that imagery is a part and parcel of advertisement in relation to effective consumer response (Greenberg & Garfinkle, 1963).The recent latest literature review suggests that there is an inclination of researchers towards the role of visuals and imagery in the effectiveness of advertisements in such a way that there has been methodological study and analysis on the significance of non-verbal cues in the rhetoric of advertisements (Swasy & Munch, 1985), (Scott, 1994a) Visual elements are analyzed in this research by drawing upon the Archival tradition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pathos is the emotionally responsible nature of speech, with regard to the ways in which the listener is attentive, impressed, and thereby increases the effect. ( (Vu, 2017) The third advertisement has been extracted from a newspaper which involves the technique of Repetition in such a way the repetition highlights the effect of milk on the health of individuals. ( (Sonesson, 1996)The visual element of this advertisement suggests the variety of Milk and the benefit that will be gained by the consuming of this product is highlighted by the specific arrangement and colors to advertise the product.…”
Section: Visual Rhetoric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Torto (2020) concluded that it is the language of the advertisement that enables consumers to identify a product and remember it. Doan (2017), found out rhetoric methods can influence the emotions of consumers.…”
Section: Related Studiesmentioning
confidence: 99%